THE CHALLENGE OF ADHD DIAGNOSIS AND ITS IMPLICATIONS (CIPEEX, 2022)
ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IS CHARACTERIZED BY INATTENTION, AGITATION AND IMPULSIVITY. ADHD CAN BE CLASSIFIED INTO THREE TYPES: INATTENTIVE, HYPERACTIVE IMPULSIVE AND COMBINED, EACH WITH ITS STRIKING FEATURE. BECAUSE IT IS A DISORDER WITH A STRONG NEUROBIOLOGICAL INFLUENCE, THE RESEARCH OF THE DIAGNOSIS AND ITS IMPLICATIONS MUST BE HANDLED IN AN INSEPARABLE WAY WITH THE PATIENT, FAMILY AND SCHOOL ENVIRONMENT, IN ORDER TO ARRIVE AT A BETTER CONCLUSION REGARDING THE TREATMENT. IN THIS SENSE, IT AIMS TO UNDERSTAND HOW THE DIAGNOSIS OF ADHD IS MADE, EVALUATING THE FALSE CONCLUSIONS ABOUT THIS DISORDER AND ITS CONSEQUENCES, FROM AN EXPANDED SUMMARY OF FIVE ARTICLES TAKEN FROM THE SITES: PUBMED, GOOGLE ACADEMMICO AND SCIELO. THE DIAGNOSIS OF ADHD IS MADE FROM THE APPLICATION OF SCALES, INTERVIEWS AND TESTS, SO THAT THESE INSTRUMENTS FOLLOW THE GUIDELINES OF THE VARIOUS EXPLANATORY MODELS. HOWEVER, THESE TOOLS AND STANDARDS STILL PRESENT IMPORTANT BARRIERS TO TREATMENT, AS THEY ARE NOT SENSITIVE AND SPECIFIC ENOUGH TO CONFIRM THE DISORDER.
Keywords: ADHD. Diagnosis. Symptoms.